Two-stage cultivation of Chlorella vulgaris using light and salt stress conditions for simultaneous production of lipid, carotenoids, and antioxidants - Ali, Hamdy Elsayed Ahmed; El-fayoumy, Eman A.; Rasmy, Wessam E.; Soliman, Ramadan M.; Abdullah, Mohd Azmuddin (Journal of applied phycology, 2021)
The effects of light and salt stress (NaCl and MgCl 2 ) on the two-stage cultivation of Chlorella vulgaris , with or without a medium replacement, for the simultaneous production of lipid, carotenoids, and antioxidant compounds were investigated. The highest lipid productivity (15.59 ± 0.10 mg L −1 day −1 ) was obtained at 5 g L −1 MgCl 2 and 140 μmol photons m −2 s −1 light intensity. The saturated fatty acids (SFA) ranged from 52.35–81.64%, monounsaturated fatty acids (MUFA) from 7.38–34.26%, and polyunsaturated fatty acids (PUFA) from 7.25–25.10%, with palmitic (C16:0), stearic (C18:0), and oleic (C18:1) acids as predominant fatty acids. Under high light intensity and nitrogen limitation in the two-stage cultivation, supplementation of 10 g L −1 NaCl with a medium replacement caused a marked increase in the total carotenoids (4.37 ± 0.33 μg mL −1 ). Cultivation of C. vulgaris in a medium containing 5 g L −1 NaCl or Mg Cl 2 , with or without a medium replacement step and with exposure to 140 μmol photons m −2 s −1 light intensity, led to enhanced antioxidant activities (65–79%). The different levels of antioxidant activities of the C. vulgaris extracts suggested the variation in the phytochemical compounds, a result of the stressed conditions. Graphical abstract